The effect of competence and work discipline on employee performance with work motivation as a mediating variable - Herry Pratama; Harif Amali Rivai; Hendra Lukito (Enrichment : Journal of Management, 2023)
This study aims to obtain empirical evidence regarding the effect of competence and work discipline on employee performance with work motivation as a mediating variable at the Regional Revenue Agency of West Sumatra Province. The population in this study were all employees of the Regional Revenue Agency of West Sumatra Province. The sampling technique is the sample method is by probability sampling with a total of 118 samples. The analytical method used is descriptive statistical analysis using SmartPLS 3.0. The results of the study show that competence and work discipline have a positive and significant effect on employee performance; competence and work discipline have a positive and significant effect on work motivation, work motivation has no effect on employee performance. Competence and work discipline have no effect on employee performance through work motivation as a mediating variable. Based on the results of the determinant coefficient test, the R square value is 0.725, this means that 72.5% of employee performance is explained by competence, work discipline and work motivation. While the remaining 27.5% is influenced by other variables not explained in this study. This study aims to obtain empirical evidence regarding the effect of competence and work discipline on employee performance with work motivation as a mediating variable at the Regional Revenue Agency of West Sumatra Province. The population in this study were all employees of the Regional Revenue Agency of West Sumatra Province. The sampling technique is the sample method is by probability sampling with a total of 118 samples. The analytical method used is descriptive statistical analysis using SmartPLS 3.0. The results of the study show that competence and work discipline have a positive and significant effect on employee performance; competence and work discipline have a positive and significant effect on work motivation, work motivation has no effect on employee performance. Competence and work discipline have no effect on employee performance through work motivation as a mediating variable. Based on the results of the determinant coefficient test, the R square value is 0.725, this means that 72.5% of employee performance is explained by competence, work discipline and work motivation. While the remaining 27.5% is influenced by other variables not explained in this study.